Association of mercury exposure with the serum high-sensitivity C-reactive protein level in Korean adults - Kim, Kisok; Park, Hyejin (Frontiers in Public Health, 2023)
Although there is evidence that mercury (Hg) exposure may be a potential risk factor for cardiovascular disease (CVD), few nationwide epidemiological researches have analyzed the association between blood Hg concentration and serum high-sensitivity C-reactive protein (hs-CRP) level as a biomarker of CVD. The present population-based national study was performed with data from the 2016–2017 National Health and Nutrition Examination Survey. In the total sample of 3,773 adults aged ≥ 20 years, the serum hs-CRP concentrations were 1.03 mg/L among participants in the lowest quartile of blood Hg level and 1.18 mg/L among those in highest quartile. The trend for the prevalence of a risky (> 1.0 mg/L) hs-CRP level (moderate risk and high risk) was significantly related to an increased quartile blood Hg concentration. After adjustment for confounders, participants with the highest quartiles of blood Hg had increased odds of a risky (> 1.0 mg/L) hs-CRP level (adjusted odds ratio = 1.34; 95% confidence interval, 1.02–1.77) compared with those with the lowest quartile of blood Hg. These findings demonstrate that a high blood Hg level increases the concentration of serum hs-CRP, a sensitive marker of chronic low-grade inflammation, and imply that the increased body burden associated with high blood Hg is a potential risk factor in the development of many inflammatory diseases, including CVD.